2003
DOI: 10.1034/j.1600-0684.2003.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative response of peripheral blood lymphocytes to mitogens in the owl monkey Aotus nancymae

Abstract: The new world primate Aotus sp. has been recommended by the World Health Organization as a model for evaluation of malaria vaccine candidates, given its susceptibility to experimental infection with the human malaria parasites Plasmodium falciparum and P. vivax. The present study examined the in vitro proliferative response of peripheral blood mononuclear cells (PBMCs) isolated from Aotus monkeys, utilizing a wide range of mitogens. Results presented herein demonstrate that the in vitro proliferative response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…As the animals were randomly chosen from a commercial farm, even if they were from the same breed, the differences in their genetic backgrounds could have contributed to the observed variations. Treatment with a combination of PMA and ionomycin activates lymphocytes, as well as other leukocytes, by mimicking the intracellular signals that occur during natural responses to antigens (20,29). A number of studies have investigated the effect of PMA-Iono on the proliferation and expression of cytokines in human and animal PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…As the animals were randomly chosen from a commercial farm, even if they were from the same breed, the differences in their genetic backgrounds could have contributed to the observed variations. Treatment with a combination of PMA and ionomycin activates lymphocytes, as well as other leukocytes, by mimicking the intracellular signals that occur during natural responses to antigens (20,29). A number of studies have investigated the effect of PMA-Iono on the proliferation and expression of cytokines in human and animal PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The increased proliferation was dependent on the cargo sequence since proliferation of PBMC treated with hTip alone or the chimeric CSKH scrambled peptide (hTip-CSKHsc) was as low as that of control cells without peptide (not shown). Some variability in Aotus response to hTip-CSKH compared to humans was observed, but this is probably due to what we have previously described for this experimental model [ 43 ]. The hTip-CSKH effect is then similar to PHA-P, that is, inducing proliferation by its own, although to a lesser extent.…”
Section: Resultsmentioning
confidence: 80%
“…The Aotus primate experimental model has proved to be useful for basic immunology and vaccination studies. The establishment of similarities is essential for physiological studies involving immune modulation, although some differences in T-cell response have been found [ 43 ]. Previously, we found that Aotus Lck was more related to Saimiri sciureus than to human Lck.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recientemente hemos caracterizado algunas moléculas de Aotus sp. que son importantes en la transducción de señales y hemos realizado estudios funcionales con células tendientes a comparar los respuestas inmunes (22)(23)(24).…”
unclassified